Role of sterol 3‐ketoreductase sensitivity in susceptibility to the fungicide fenhexamid in Botrytis cinerea and other phytopathogenic fungi. Issue 5 (9th November 2012) - Debieu, Danièle; Bach, Jocelyne; Montesinos, Emeline; Fillinger, Sabine; Leroux, Pierre
Abstract BACKGROUND The narrow‐spectrum fungicide fenhexamid was introduced into French vineyards in 2000 to control grey mould caused by a complex of two cryptic species: Botrytis cinerea, the predominant species sensitive to fenhexamid, and Botrytis pseudocinerea, naturally resistant. Fenhexamid was suggested to inhibit the 3‐ketoreductase involved at C‐4 demethylation steps during ergosterol biosynthesis, as revealed by its effects on the B. cinerea sterol profile. Resistance monitoring studies have hitherto identified two B. cinerea fenhexamid‐resistant phenotypes, both resulting from mutations in the erg27 gene encoding 3‐ketoreductase. RESULTS The role of 3‐ketoreductase sensitivity in fungal susceptibility to fenhexamid was investigated by studying sterol profiles and microsomal 3‐ketoreductase in various fungal strains. Fenhexamid does inhibit B. cinerea 3‐ketoreductase activity. Erg27 mutations causing amino acid substitutions in or near the transmembrane domain strongly decrease the affinity of fenhexamid for 3‐ketoreductase. Fenhexamid has very low affinities for 3‐ketoreductase in inherently resistant species, whether closely related to B. cinerea, like B. pseudocinerea, or more distantly related, like Nectria haematococca. CONCLUSION erg27 mutation and erg27 polymorphism may therefore contribute to the unfavourable binding of fenhexamid to its target, 3‐ketoreductase, explaining the acquisition of fenhexamid resistance in B. cinerea and the narrow spectrum of this fungicide.© 2012 Society of Chemical Industry